Scientific analysis in traditional preventive measures using garlic and vinegar as a wood fungicide in Malaysia - Barkeshli, Mandana; Abdul Rahim, NurulAdida (Sukriti Nikunj, 2014)
Information received from woodwork masters (Carpenters) indicate that garlic (Allium Sativum) and vinegar are being traditionally applied on timbers as fungicide against wood staining and mould fungi in Malaysia. This technique can reduce the usage of synthetic fungicides such as Boric acid, Arsenic compound, Zinc chloride and Tributyltin oxide, which may cause harm to human health, artefacts and environment also. During the present study the experiment was conducted to observe antifungal activities of vinegar and garlic extraction. The extraction was used against the culture of Aspergillus niger on agar media and kept at a temperature of 35o C-37o C for inoculation in the laboratory. The results indicate that the extracts of garlic and vinegar completely inhibited the fungi after a certain period of time.